2014
DOI: 10.5539/ass.v10n7p200
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Specific Advertising Media (AM): Informative or Manipulative?

Abstract: Attitudes toward advertising in general (A G ) is a concept which often raises ethical, social and cultural concerns, and yet in the context of specific media, consumers are often more positive, and find advertising entertaining, thought-provoking, amusing and informative. This paper focuses on attitudes toward advertising in three specific media (A M ) (print, television and online advertising) and aims to provide input into the design decisions of an advertising campaign. The survey is based on a sample of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…Perceived entertainment has a positive effect on consumer attitudes toward advertising [16,31,33]. Some past studies [34][35][36] identified that consumers perceive advertising helpful in improving their social roles and image. Advertising often presents the imaginary situation showing how consumer will feel and look after using the advertised brand.…”
Section: Personal Utility Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived entertainment has a positive effect on consumer attitudes toward advertising [16,31,33]. Some past studies [34][35][36] identified that consumers perceive advertising helpful in improving their social roles and image. Advertising often presents the imaginary situation showing how consumer will feel and look after using the advertised brand.…”
Section: Personal Utility Beliefsmentioning
confidence: 99%
“…Personal utility beliefs explain how an individual perceives the advertising at personal level. At personal level consumers perceive advertising as informative, entertaining and helpful in improving social role and image [27,35,36,50]. Socioeconomic beliefs explain consumers' macro perceptions of advertising.…”
Section: Theoretical Foundations and Conceptual Modelmentioning
confidence: 99%
“…Furthermore, the idea of executing a content that is current and entertaining could get consumers to interact electronically in an effective way. This powerful attribute can be seen as a future of advertising and may become more figurative in consumers' minds than television advertising as a marketing stimulus that stands out relative to others in their environment (Yaakop & Hemsley-Brown, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Esse modelo servia até a disseminação da Internet e sua conseqüente relação com mobilidade urbana. Esse ambiente não prevê facilidade para a gestão das privacidades, mas sabe-se que, nesse contexto, os consumidores são muitas vezes mais positivos e encontram publicidade divertida, provocadora, divertida e informativa (Yaakop & Hemsley-Brown, 2014). Para alguns autores, esse ambiente divertido torna-se uma ameaça para o bem-estar dos consumidores, principalmente, no que se refere a hábitos alimentares.…”
Section: O Bem Estar E a Regulamentação Publicitáriaunclassified